Early life programming by diet can play a role in risk reduction of otitis in dogs - Hemida, Manal B. M.; Vuori, Kristiina A.; Borgström, Nona C.; Moore, Robin; Rosendahl, Sarah; Anturaniemi, Johanna; Estrela-Lima, Alessandra; Hielm-Björkman, Anna (Frontiers in Veterinary Science, 2023)
Introduction Otitis in dogs is often chronic while local treatment primarily consists of flushing, antibiotics, and/or antifungals. We were interested in finding early life variables that associate with otitis later in life, preferably some that could be modified. Methods A cross-sectional hypothesis-driven study with longitudinal data was performed to search for associations between pre- and postnatal exposures, and the incidence of owner-reported otitis in dogs at over 1 year of age. The multivariate logistic regression analysis study included data from 3,064 dogs and explored 26 different early life variables at four early life stages: prenatal, neonatal, postnatal, and puppyhood. We compared two feeding patterns, a non-processed meat-based diet (NPMD, raw) and an ultra-processed carbohydrate-based diet (UPCD, dry). Results We report that eating a NPMD diet significantly decreased the risk of otitis later in life, while eating a UPCD diet significantly increased the risk. This was seen in different life stages of mother or puppy: The maternal diet during pregnancy (p=0.011) and the puppies’ diet from 2 to 6 months of age (p=0.019) were both significantly associated with otitis incidence later in life, whereas the puppies’ first solid diet, was associated in the same way, but did not reach significance (p=0.072). Also, analyzing food ratios showed that when puppies were consuming >25% of their food as NPMD it significantly decreased their incidence of otitis later in life, while a ratio of >75% UPCD in their diet significantly increased their risk of otitis. Also, if the dog was born in the current family, was exposed to sunlight for more than 1 hour daily, and was raised on a dirt floor during puppyhood, there was a lower risk of otitis development later in life. Discussion The findings only suggest causality, and further studies are required. However, we propose that veterinarians, breeders, and owners can impact otitis risk by modifying factors such as diet and environment.